Impact of intellectual disability on longitudinal arch and symmetry of the lateral and medial load of the foot - Marta Bibro; Agnieszka Jankowicz-Szymańska; Katarzyna Wódka; Małgorzata Łaczek-Wójtowicz (University of Applied Sciences in Tarnow, Poland, 2019)
Background: In the population of people with intellectual disabilities (ID) there is a frequent occurrence of bone deformities and orthopedic problems affecting the feet as well. They are associated with a change of the loading of the feet. It affects the deterioration of the functional efficiency of the feet, often contributes to discomfort, pain and predisposes to the development of adverse changes in the upper body segments. The aim of the study was to assess the impact of intellectual disability in participants with aetiology other than Down's syndrome on longitudinal arching and symmetry of lateral and medial load of the foot. Materials and methods: There were 38 participants with mild and moderate intellectual disability, with an average age of 23 years and 44 young non-disabled people with an average age of 20.8 under research. The main measurement tool used to assess the arching and loading the foot zones was the BTS P-WALK platform. The measurement included analysis in terms of statics and lasted 30s. Results: The comparison of both groups showed no significant differentiation in the medial and lateral load of the forefoot and rearfoot. Among people with ID correct arches of the feet were observed in 52.6% of participants in the right foot and 57.9% of the left foot, while in the control group in 56.9% in both the right and left foot. People with intellectual disabilities were characterized by a higher rate of flatfoot in relation to the control group. The hollow foot was more frequently observed in control group than in people with ID. Conclusions: In people with intellectual disabilities with aetiology other than Down's syndrome, flat feet are diagnosed more often than in healthy peers who do not differ in body weight and BMI. Intellectual disability is associated with a greater loading of the medial part of the forefoot.